2013
DOI: 10.1016/j.physa.2013.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Threshold model of cascades in empirical temporal networks

Abstract: Threshold models try to explain the consequences of social influence like the spread of fads and opinions. Along with models of epidemics, they constitute a major theoretical framework of social spreading processes. In threshold models on static networks, an individual changes her state if a certain fraction of her neighbors has done the same. When there are strong correlations in the temporal aspects of contact patterns, it is useful to represent the system as a temporal network. In such a system, not only co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 21 publications
(18 reference statements)
2
92
0
Order By: Relevance
“…Threshold models can be generalized to temporal networks in several ways. Reference [23], for example, considers a sliding window where only contacts within the window matters for the spreading. The authors examined two types of threshold rules–whether the threshold operates on all the total number of contacts with I in the interval or on the fraction of such contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Threshold models can be generalized to temporal networks in several ways. Reference [23], for example, considers a sliding window where only contacts within the window matters for the spreading. The authors examined two types of threshold rules–whether the threshold operates on all the total number of contacts with I in the interval or on the fraction of such contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed * kgoh@korea.ac.kr that, for a wide range of network densities and threshold distributions, even an extremely small seed fraction ρ 0 can activate a finite fraction of an infinite-size network, an event called a global cascade [16,17]. Recently, some studies have generalized the threshold model to temporal networks [22] and to multiplex networks [5,23]. However, cascades with heterogeneous nodal responses to their multiplex environments are not yet addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [21] discusses this further and uses a sliding time window to represent the duration of possible influence. Ref.…”
Section: B Models For Spreading Processesmentioning
confidence: 99%